(3TQM bUjOI GdfGHZI GdPHjGfis - (3eLghds
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje CMb GdecGfI HGdEaJJGM bGd GdfGHZI GdPHjGfi hCeSg RjGO Hf eYGhjg Hf LGHQ hCHh YbQH hgh ef GdTYQGA GdLGgdjI s
(3BNQgG (B:s
( (3GdejcQhajde ZjQ hGVM ai GdJUhjQ (B) s
(3eUhQI Ydi hQbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdCOHs